Rosa multiflora Thunb.: Chemical composition, potential pharmaceutical applications, and future research directions - Le Pham Tan Quoc; Pham My Hao; Pham Thi Quyen; Lam Bach Bao Phuong (Natural Resources for Human Health, 2026)
Rosa multiflora Thunb., is a widely distributed plant species of the Rosaceae family and used in traditional medicine in many Asian countries. In recent years, this species has attracted increasing attention in the field of medicinal research due to its high content of bioactive compounds. This article aims to systematically evaluate the morphological characteristics, secondary chemical constituents, and major biological activities of R. multiflora, such as antioxidant, antibacterial, and anti-inflammatory properties. Studies have shown that this species contains significant amounts of flavonoids, phenolic acids, tannins, triterpenoids, and carotenoids, which contribute to its potential biological effects. However, most of the studies have only been conducted at the in vitro level, lacking clinical studies and in vivo trials to determine the actual efficacy and safety. Therefore, further in-depth studies are needed to optimally exploit the value of R. multiflora in pharmaceutical applications and the functional food industry.